Isolation and Diagnosis of Bacteria in Bacteremia Patients and Study Their Resistance to Antibiotics in Kirkuk Hospitals - Al-Wandawy, Abbas Hameed; Abdulhady Zwain, Luma; Maher Khidher, Dalia Maher Khidher; Farag, Peter F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
313 blood samples were collected from bacteremia patients, including 146 samples (30 from patients and 116 from outpatients) from Azadi teaching hospital, 36 samples from the dialysis unit at Kirkuk General Hospital, 126 samples (42 from inpatients and 84 from outpatients) from the Children’s Hospital, and 5 samples from the Women’s and Obstetrics Hospital in Kirkuk province, for the period from January 24, 2022, to September 10, 2022. The study, including the isolation and diagnosis of bacteria and the study of their resistance to antibiotics, The results show that 32 (17.87%) positive growth cultures were obtained from febrile patients, 3 (8.33%) from dialysis patients in the dialysis unit, and 15 (65.21%) from burn and wound patients. Fifty bacterial isolates were obtained, all of which were gram-positive. Staphylococcus was the highest with 28 isolates, including [(11) S.homoinis, (4) S.epidermidis epidermidis, (2) isolates each of S.haemolyticus and S. Wagner, and (9) Staphylococcus spp.], while Enterococcus faecalis was one isolate. The gram-negative bacteria were [(11) Pseudomonas aeruginosa, (5) Escherichia coli, (2) isolates of Enterobacter cloacae, and followed by one isolate of Raoultella terrigena, Acinetobacter spp., and Klebsiella spp.). Staphylococcus spp. resistance to 20 antibiotics was studied, and the species S.homoinis showed 100% resistance to (Oxacillin, Benzylpenicillin, and Amoxicillin). Whereas S.epidermidis epidermidis was 100% antibiotic-resistant (Oxacillin, Benzylpenicillin, and Amoxicillin). S. hemolyticus was resistant to (erythromycin, benzylbeniclin, amosiclin, amikachin, gentamicin, torramichin, and tetracycline) by 100%. S. warneri was resistant to (oxacillin, benzylpenicillin, amoxicillin, and dusidic Acid) at a rate of one hundred percent.